From preciousness to outdoors, refuge as fiction - Miquel Bartual, Mijo (Escritura e Imagen, 2020)
In this paper, we address the progressive precarization and uncertainty, both conceptual and material, in which we find ourselves, analyzing the reflex movement by which we seek shelter, trying to generate security in what can only bring sacrifice. With the outbreak of the health crisis, biopolitical parameters and political priorities have shown that this movement can only be a step backwards, if it does not start from the prior acceptance of our common destiny on the planet. We propose a modification of the concept of progress that could accommodate other possible futures, subverting the meaning that modernity had given it and opening it up to the possibility of progress towards the end.
Keywords: Precarization; shelter; health crisis; climate change; new stories